Kryzys kultury europejskiej w ujęciu Leszka Kołakowskiego - Turoń-Kowalska, Agnieszka (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Drawing on the Heglian interpretation of history, which suggests that no epoch is able to properly identify itself, Leszek Kołakowski ponders the crisis of the 20th-century European civilization. Not knowing the fundamentals of one’s own culture is defined by the philosopher as an aspect of postmodern Europe. An attempt at defining one’s own civilization is to be simultaneously an effort made to define oneself — a human being. For Kołakowski, the problem of postmodernity results from the triumph of rationality, in particular the idea of modern rationality. Therefore, the analysis of European culture is to be merely a stimulus to investigate the condition of European civilization, namely its intellectual condition, but also, and more importantly, an attempt at answering the question on how to deal with the decay of humanism, the collapse of values and “the idolatry of politics.” Kołakowski points out to the spirit of self-criticism and uncertainty, which is the feature of European culture and turns out to be an opportunity to uphold its spiritual certainty. Key words: Leszek Kołakowski, European civilization, the crisis of culture, “the idolatry of politics”